POTENSI HIPOGLIKEMIA DAN HIPERGLIKEMIA PADA PASIEN DIABETES MELITUS TIPE 2 AKIBAT INTERAKSI OBAT - Yardi Saibi; Delina Hasan; Bukhoriah Safitri; Vidia Arlaini Anwar (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
The potency of drug interaction is higher because of the presence of comorbidities and polypharmacy in type 2 diabetes mellitus patient. This study aimed to know the potency of drug interaction event in type 2 diabetes mellitus patient in one of hospital in Jakarta in 2016 which have potency to cause hypoglycemia and hyperglicemia. Data was collected from medical record of type 2 diabetes mellitus patient . The design of this research was cross- sectional. Data retrieval was conducted retrospectively. The sample size in this study was 151 Diabetes mellitus type 2 patients medical record who received antidiabetes and met the inclusion and exclusion criteria. Data analysis was done statistically using univariate analysis . Results showed that female dominated the patient as much as 74,83% with hypertension as the most common comorbidities as much as 28,48%. There were 186 drug interaction event potency with 83,8% of them could cause hypoglicemia while the rest could cause hyperglicemia. Drug interaction with the potency that can cause either hypoglycemia and hyperglycemia that can effect the failure to get the therapeutic goal still be frequent found in patient prescription. Drug interaction event should get appropriate attention from clinical pharmacist in hospital